IDEOLOGICAL AND AESTHETIC PRINCIPLES OF THE WRITER IN THE NOVEL "EMIR TEMUR" (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the ideological and artistic position of Azerbaijani writer Yunus Oguz in his novel "Emir Temur," which consists of two parts: "Rise" and "Ruler of the World." The novel reveals the personality of the famous Eastern ruler Timur as a diplomat, military strategist and tactician, and statesman. The novel depicts the ruler's diplomatic activities, receiving ambassadors from various states, and his correspondence with rulers of many countries, reflected in various episodes and stories. Through the image of the great ruler, the work reveals the peculiarities of medieval diplomacy, political relations, and cultural life.